Serologic responses to peptides of Anaplasma phagocytophilum and Borrelia burgdorferi in dogs infested with wild-caught Ixodes scapularis. (August 2017) - Chandrashekar, R.; Beall, M.J.; Thatcher, B.; Saucier, J.M.; Tyrrell, P.; Lappin, M.R.
Highlights: Evaluated antibody levels to VlsE of B. burgdorferi and p44 of A. phagocytophilum . Antibiotic treatment reduced C6 antibody levels within 12 weeks. Antibodies to the APH-4 peptide of p44 could be detected earlier post-infection. A. phagocytophilum DNA was detected in peripheral blood 77 days post-infection. Decreasing C6 antibody levels may help indicate control of B. burgdorferi infection. Abstract: Anaplasma phagocytophilum and Borrelia burgdorferi are both transmitted by Ixodes spp. and are associated with clinical illness in some infected dogs. This study evaluated canine antibody responses to the A. phagocytophilum p44 peptides APH-1 and APH-4 as well as the B. burgdorferi C6 peptide before and after doxycycline treatment. A total of eight dogs were infested with wild-caught I. scapularis for 1 week. Blood was collected prior to tick attachment and from Days 3–77 to 218–302 with doxycycline treatment beginning on Day 218. Blood was assayed for A. phagocytophilum DNA by PCR assay. Sera was assessed for antibodies by immunofluorescent antibody (IFA) test and ELISA. Anaplasma phagocytophilum DNA was amplified from blood of all dogs by Day 7. Antibodies to APH-4 were detected in serum as early as 14 days after tick exposure and six dogs had APH-4 antibodies detected 3–7 days before antibodies against APH-1. All dogs were seropositive for A. phagocytophilum from Days 218 to 302. Antibodies to B. burgdorferi were detected in 6/8 dogs beginning 21 days after I. scapularis infestation. Among the five dogs that remained seropositive at Day 218, C6 antibody levels declined on average 81% within 84 days of initiating treatment. The results suggest that the APH-4 peptide may be more useful than APH-1 for detecting antibodies earlier in the course of an A. phagocytophilum infection. After doxycycline administration, C6 antibody levels but not APH-1 or APH-4 antibody levels decreased, suggesting a treatment effect on C6 antibody production.